Pengaruh Jumlah Penduduk, Indeks Pembangunan Manusia dan Pertumbuhan Ekonomi Terhadap Tingkat Kemiskinan Pada Kabupaten/Kota Provinsi Kalimantan Selatan - Nur Alya Hayati; Lina Suherty (PPJP ULM, 2025)
This research aims to determine the effect of population size, human development index and economic growth on poverty levels in the districts/cities of South Kalimantan Province. This type of research is quantitative using a panel data regression analysis method with a Random Effect Model (REM) approach. The data used is secondary panel data for the 2012-2021 period. The results of this research show that simultaneously and partially Population Number, Human Development Index and Economic Growth have a significant effect on Poverty Levels in Districts/Cities in South Kalimantan Province. Meanwhile, the variable that has the most influence on the level of poverty in the districts/cities of South Kalimantan province is the Human Development Index.